PENGGUNAAN SMS SEBAGAI MEDIA INFORMASI DAN KONSULTASI KESEHATAN BAGI MASYARAKAT PEDESAAN - Uud Wahyudin; Eni Maryani (Avant Garde, 2017)
The development of technology always produces both positive and negativeimpacts, as well as the use of mobile phones in public. Today, short messageservices, known better as SMS, as a functionof mobile phones has been quitepopular to some people in rural areas in West Java.This paper describes the useof SMS in mobile phoneinthe process ofinformation seeking for health informationand services for community. This research was conducted through descriptiveapproach with in-depth interview, observation and literature study.The resultsshows that the development of SMS has become the channelfor informationseeking onhealth information and services. This system is usefull and hasbeendevelopedby the government and stakeholders engaged in public health toprovidethe information for health services. In general, SMS usage is consideredsuccessful and needs to be expanded by both government and non-governmentalorganizations due to several purposes.Firstly, the use of mobile phones hasbecome part of information seekingin rural communities.Secondly, the use of SMSin supplying health information and services can provide a faster informationsystem related to hospital services and patient’s condition. On the top of that, thedissemination of health information and services through SMS also providesopportunities for better communication between healthcare providers and patientin more deepen and intensive way.